196k views
1 vote
-9x - 5y = 26
4x -4y = -24

User Jook
by
5.1k points

1 Answer

2 votes

Answer:

(-4, 2)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination
  • Solving systems of equations by graphing

Explanation:

Step 1: Define systems

-9x - 5y = 26

4x - 4y = -24

Step 2: Rewrite systems

4x - 4y = -24

  1. Add 4y to both sides: 4x = 4y - 24
  2. Divide 4 on both sides: x = y - 6

Step 3: Redefine systems

-9x - 5y = 26

x = y - 6

Step 4: Solve for y

Substitution

  1. Substitute in x: -9(y - 6) - 5y = 26
  2. Distribute -9: -9y + 54 - 5y = 26
  3. Combine like terms: -14y + 54 = 26
  4. Isolate y term: -14y = -28
  5. Isolate y: y = 2

Step 5: Solve for x

  1. Define original equation: 4x - 4y = -24
  2. Substitute in y: 4x - 4(2) = -24
  3. Multiply: 4x - 8 = -24
  4. Add 8 to both sides: 4x = -16
  5. Divide 4 on both sides: x = -4

Step 6: Graph

Check the solution set.

-9x - 5y = 26 4x -4y = -24-example-1
User Bijou
by
5.0k points